Exploring cultural goods : new perspectives on consumer behaviour in Italy - Castiglione, Concetta (Trinity College (Dublin, Ireland). Department of Economics, 2013)
The socioeconomic composition of attendance at the arts has interested researchers and policy-makers for decades and re-emerges as an issue every few years. This thesis studies cultural attendance in Italy and its main determinants. For this, extensive econometric analysis is carried out using specifically constructed datasets. It aims to extend the cultural participation literature which has mosdy concentrated on the US to date, by offering an empirical analysis of the Italian cultural participation, specifically theatre, and adopting a new approach to cultural capital.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.